2004
DOI: 10.3346/jkms.2004.19.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal Relapse in a Patient with Acute Promyelocytic Leukemia: A Case Report and Review of the Literature

Abstract: The involvement of central nervous system is rare in acute promyelocytic leukemia (APL). We report a APL patient of a 41 yr-old Korean male who presented with fever and petechia. Complete molecular remission was achieved with all-trans retinoic acid (ATRA), idarubicin, and cytarabine. Ten months later, he complained of a mild headache. The results of the physical examination and the complete blood counts were normal. The examination of cerebrospinal fluid showed the presence of promyelocyte. Bone marrow studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Headache, vertigo, nausea, vomiting, visual disturbance, motor weakness and seizure could be the presenting symptoms of APL in CNS 9. Our patient had non-specific mild headache accompanied with herpetic skin lesions at the first CNS relapse.…”
Section: Discussionmentioning
confidence: 64%
“…Headache, vertigo, nausea, vomiting, visual disturbance, motor weakness and seizure could be the presenting symptoms of APL in CNS 9. Our patient had non-specific mild headache accompanied with herpetic skin lesions at the first CNS relapse.…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study, 20/31 patients relapsed. The duration of remission ranged between 1 and 144 months, with a median of 5 months (22). The present study was reported 20 months subsequent to the initial diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Involvement of the CNS from APML is rare, affecting only 1% of patients [17]. The most common symptoms at CNS relapse include headache, nausea, vomiting, and seizure [9]. Risk factors for developing APML in the CNS include a high circulating blast count, elevated lactate dehydrogenase activity, and having one of the monocytic leukemic subtypes [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have appeared in recent literature of acute promyelocytic leukemia (APML) occurring in patients with MS following mitoxantrone treatment [1][2][3][4][5][6][7][8]. While central nervous system (CNS) involvement in APML is uncommon [9][10][11][12], APML involvement of the optic nerves is extremely rare and to the best of our knowledge only one report exists [13]. Following the widespread use of all-trans-retinoic acid (ATRA) and modern chemotherapy regimens that avoid high-dose cytarabine consolidation [14], reports of extramedullary relapses, most frequently involving the CNS have appeared [15].…”
Section: Introductionmentioning
confidence: 99%